ROTOR: Part II Transdiciplinary dialogue and debate - McAra, Catriona; Swindells, Steve (University of Huddersfield Press, 2013)
ROTO? is a two-year programme of exhibitions, public events and talks at Huddersfield Art Gallery featuring the transdisciplinary work of art and design staff from the University of Huddersfield. Now in its second year, ROTO? showcases a community of artists, designers and curators whose ideas and connective practices migrate and span artistic production, techno-design research, craft and cultural studies. ROTO? is located at the pivot between art and design disciplines and society, where points of intersection and engagement are considered and debated from multiple perspectives. The programme signals a unique partnership between Huddersfield Art Gallery and the University of Huddersfield to present a broad spectrum of practices and dialogues. Each exhibition features a number of public events in the form of artist/designer and curator talks.